2014
DOI: 10.1108/pijpsm-03-2013-0028
|View full text |Cite
|
Sign up to set email alerts
|

Police chief leadership: styles and effectiveness

Abstract: Purpose – The purpose of this paper is to examine the leadership styles of police chiefs and how these styles related to demographic, personality, and effectiveness. Design/methodology/approach – Participants included 161 police chiefs in Texas who completed the Multifactor Leadership Questionnaire (MLQ 5X-Short) leader form, the NEO Five-Factor Inventory (NEO-FFI), and a background characteristics form. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 23 publications
0
40
1
Order By: Relevance
“…In a previous study utilizing the multifactor leadership questionnaire (MLQ), Densten (1999) found that police officers used significantly less transformational leadership than the norm and were most likely to manage by exception. Overall, the existing literature on this topic that there is no consensus on the predominant or most effective leadership style in the police (Sarver and Miller, 2013). One important reason for these inconclusive findings could be the organizational culture of the police, which puts a lot of emphasis on rank structures and promotes the assertive and strong leader (Manning, 1997;Crank, 2004;Reuss-Ianni and Ianni, 1983) and "a cult of masculinity that implies the 'celebration' of the use of force and violence against criminals and other disreputable groups" (Vera and Koelling, 2013, p. 68).…”
mentioning
confidence: 99%
“…In a previous study utilizing the multifactor leadership questionnaire (MLQ), Densten (1999) found that police officers used significantly less transformational leadership than the norm and were most likely to manage by exception. Overall, the existing literature on this topic that there is no consensus on the predominant or most effective leadership style in the police (Sarver and Miller, 2013). One important reason for these inconclusive findings could be the organizational culture of the police, which puts a lot of emphasis on rank structures and promotes the assertive and strong leader (Manning, 1997;Crank, 2004;Reuss-Ianni and Ianni, 1983) and "a cult of masculinity that implies the 'celebration' of the use of force and violence against criminals and other disreputable groups" (Vera and Koelling, 2013, p. 68).…”
mentioning
confidence: 99%
“…The effectiveness of TFL has been proven by many researchers from their studies. Sarver & Miller, (2014) has demonstrated positive relationship between TFL and firm effectiveness. Rather than using proxy variables from archival sources or demographic data as done by many other scholars, using direct measures of personality and leadership resulted in the mean levels of conscientiousness of the top management team members and chief executive officer both directly related to organizational performance (Birasnav, 2014).…”
Section: 1effect Of Tflmentioning
confidence: 97%
“…Samad (2012) have also claimed that TFL has a significant positive impact on team performance and, on the contrary, transactional leadership has a significant negative effect on team performance. Two dimensions of psychological empowerment were highlighted (Colbert & Bradley, 2014, Sarver & Miller, 2014& Mason, Griffin, & Parker, 2014, namely, meaning and self-determination which have partial mediation effect in the relationship between TFL and team performance. Another attempt by using 61 R&D teams from 32 Taiwanese high-technology firms stated that TFL was positively related to positive team goals, which, in turn, positively predicted positive group effect (Fisher, 2013).…”
Section: 3effect On Team Performancementioning
confidence: 99%
“…Research has also been conducted into police leadership from the perspective of style theory (Bruns & Shuman, 1988;Kuykendall & Unsinger, 1982;Murphy & Drodge, 2004), role theory (van Dijk et al, 2015;White, 2014). The effectiveness of managerial behaviour has also been addressed (Densten, 2003;Sarver & Miller, 2014;Schaefer, 2008Schaefer, , 2010.…”
Section: Research On Managerial Work Within the Policementioning
confidence: 99%
“…Most research focused on perceptions of managerial work rather than objective measures. Also, neo-charismatic theories, such as transformational leadership (Bass, 1985;Burns, 1978) have gained considerable traction within the police (for example, Alison & Crego, 2008;Barth-Farkas & Vera, 2014;Cockcroft, 2013;Densten, 1999;Gobby et al, 2004;Sarver & Miller, 2014;Silvestri et al, 2013).…”
Section: Research On Managerial Work Within the Policementioning
confidence: 99%